2010
DOI: 10.2337/dc10-0561
|View full text |Cite
|
Sign up to set email alerts
|

Double Heterozygous Mutations Involving Both HNF1A/MODY3 and HNF4A/MODY1 Genes

Abstract: OBJECTIVEWe describe a maturity-onset diabetes of the young (MODY) case with mutations involving both HNF4A and HNF1A genes.RESEARCH DESIGN AND METHODSA male patient was diagnosed with diabetes at age 17; the metabolic control rapidly worsened to insulin requirement. At that time no relatives were known to be affected by diabetes, which was diagnosed years later in both the parents (father at age 50 years, mother at age 54 years) and the sister (at age 32 years, during pregnancy).RESULTSThe genetic screening s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…It is therefore unlikely to be causative of MODY. The proband described by Forlani et al was heterozygous for HNF1A E508K and HNF4A R80Q. Both mutations are novel and while a different mutation, R80W, has been reported in HNF4A , further evidence to support the pathogenicity of E508K is lacking.…”
Section: Discussionmentioning
confidence: 98%
“…It is therefore unlikely to be causative of MODY. The proband described by Forlani et al was heterozygous for HNF1A E508K and HNF4A R80Q. Both mutations are novel and while a different mutation, R80W, has been reported in HNF4A , further evidence to support the pathogenicity of E508K is lacking.…”
Section: Discussionmentioning
confidence: 98%
“…The p.E508K variant has been reported in 2 published articles, 35,36 both reporting on individuals with MODY. In 1 case, a family member had early onset diabetes (age 17 years), and carried both HNF1A p.E508K and a mutation in HNF4A , p.R80Q.…”
Section: Discussionmentioning
confidence: 99%
“…The father from whom p.E508K was inherited was diagnosed with type 2 diabetes at age 57 years. 35,36 The finding of these variants in patients with MODY suggested that they might be high-penetrance alleles. Our study in large populations without ascertainment bias for early-onset showed that p.E508K was associated with a 5-fold increase in prevalence, but incomplete penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…In previously reported pathogenic MODY mutations, homozygosity causes a severe, early-onset phenotype. In addition, there has never been a report of a patient homozygous for mutations in HNF1A [13,14]. The variant c.1663C>T is a missense mutation in exon 9 which is specific to the A isoform of HNF1A .…”
Section: Discussionmentioning
confidence: 99%